Low-viscosity modified rubber asphalt
By microwave activation treatment and chemical modification of rubber powder, combined with expanded graphite and titanium dioxide modified expanded graphite, the problem of high viscosity of rubber asphalt at high temperature is solved, and the preparation of rubber asphalt with low viscosity and high thermal stability is achieved. It is suitable for Pavement materials.
Patent Information
- Application Number
- CN202411552762.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2020-09-29
- Publication Date
- 2025-02-25
AI Technical Summary
The existing rubber asphalt has high viscosity at high temperatures, which increases the difficulty of spreading and compacting, and has low thermal stability, which affects the long-term use of the road surface.
By using microwave to activate the waste tire rubber powder, combined with chemical substances such as hydrogen peroxide, ferrous sulfate and polyvinylpyrrolidone, expandable graphite and titanium dioxide modified expanded graphite are added to the modified asphalt to reduce viscosity and improve thermal stability.
The preparation of low-viscosity rubber asphalt is realized, which reduces the viscosity of asphalt, and improves its thermal stability and anti-fume release performance. It is suitable for pavement materials.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rubber asphalt, in particular to a low-viscosity modified rubber asphalt. Background Art
[0002] Rubber asphalt is a modified asphalt binder material formed by first processing the original material of waste tires into rubber powder, then combining them according to a certain coarse and fine grading ratio, adding a variety of high polymer modifiers, and fully melting and expanding with the matrix asphalt under high temperature conditions (above 180°C) with full mixing. Rubber asphalt has greater elasticity and elastic recovery ability at high temperatures, which can improve the road surface's resistance to deformation and fatigue cracking; it has good high and low temperature performance, reducing the sensitivity of asphalt to temperature; it has the characteristics of high viscosity, anti-aging, and strong antioxidant ability; it has strong anti-skid function, reduces water splashing during driving in rainy days, improves vision, reduces noise, and greatly improves road driving safety and comfort; rubber asphalt uses waste tire rubber as raw material, so its preparation is beneficial to environmental protection, saving natural resources, and improving the living environment of human beings. Therefore, rubber asphalt is currently widely used. However, the existing rubber asphalt has a high viscosity at high temperatures, which increases the difficulty of asphalt spreading and road compaction, and its processing equipment is complex and not easy to store stably for a long time, which is not conducive to the long-term use of the road surface, and the amount of rubber consumed is large.
[0003] Therefore, low-viscosity rubber asphalt came into being. Low-viscosity asphalt reduces the amount of rubber powder used, adopts high-intensity treatment technology or chemical modification to promote the full desulfurization and depolymerization reaction of vulcanized rubber powder in the matrix asphalt, and restores it to a plastic state of recycled rubber, thereby greatly reducing the viscosity of the binder; low-viscosity rubber asphalt also has better resistance to emission cracking and fatigue cracking, so it is a very popular paving material. However, the reduction of rubber asphalt viscosity will also lead to a decrease in the thermal stability of the asphalt binder. The high-temperature performance of low-viscosity rubber asphalt is lower than that of high-viscosity rubber asphalt under the same conditions; therefore, the development of low-viscosity rubber asphalt requires both high thermal stability and low viscosity. Summary of the invention
[0004] The object of the present invention is to provide a low-viscosity modified rubber asphalt and a preparation method thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a low-viscosity modified rubber asphalt, which comprises the following raw materials, by weight: 78 to 85 parts of modified asphalt, 10 to 17 parts of activated rubber powder, 12 to 15 parts of styrene-butadiene-styrene block copolymer, and 12 to 15 parts of softening oil.
[0006] Furthermore, the modified asphalt is prepared from base asphalt and a modifier.
[0007] Furthermore, the activated rubber powder is mainly prepared by reacting waste tire rubber powder, hydrogen peroxide, ferrous sulfate and polyvinyl pyrrolidone.
[0008] Furthermore, the modifier is made of expanded graphite, hydrogen peroxide and silicone oil. The expanded volume of the expanded graphite is ≥400 ml / g, the ash content is <0.2%, the moisture content is <3%, and the oxidizability is <35 mg / g﹒h.
[0009] Furthermore, the mass ratio of the base asphalt to the modifier is 1:0.008-0.03.
[0010] Furthermore, the matrix asphalt is any one of 70#, 90#, and 200#.
[0011] Furthermore, the particle size of the waste tire rubber powder is 40 to 80 meshes.
[0012] Furthermore, the softening oil is any one or more of castor oil, aromatic oil, naphthenic oil, furfural oil, and rubber filler oil.
[0013] A method for preparing low-viscosity modified rubber asphalt comprises the following steps: (1) Preparation of activated rubber powder: (2) Preparation of modified asphalt: (3) Preparation of viscosity-modified rubber asphalt products.
[0014] Further, a method for preparing low-viscosity modified rubber asphalt comprises the following steps; (1) Preparation of activated rubber powder: Take waste tire rubber powder and irradiate it with microwaves; add 30% hydrogen peroxide solution and ferrous sulfate, react, filter, and dry; add polyvinyl pyrrolidone solution, stir, heat to 75-80°C, react for 15-20 minutes; irradiate with microwaves to obtain activated rubber powder; (2) Preparation of modified asphalt: tetrabutyl titanate, anhydrous ethanol and glacial acetic acid are mixed and stirred, and concentrated sulfuric acid is slowly added, stirred at high speed, and reacted; expanded graphite is added, the temperature is raised to 50-55°C, and reacted; the temperature is raised to 78-82°C, the anhydrous ethanol is removed, the mixture is dried, silicone oil is added, and stirred to obtain a modifier; The base asphalt is heated to 185-190°C, stirred, and a modifier is added; and the modified asphalt is obtained by high-speed shearing. (3) Preparing a low-viscosity modified rubber asphalt product; mixing the modified asphalt and softening oil, stirring, and developing; adding the activated rubber powder and styrene-butadiene-styrene block copolymer prepared in step (1), stirring; heating to 180-190° C.; high-speed shearing, heating to 205-225° C., high-speed stirring, maintaining a constant temperature, and developing; obtaining a low-viscosity modified rubber asphalt product.
[0015] The present invention uses microwaves to treat the surface of waste tire rubber powder. After microwave radiation, the cross-linked bonds, sulfur-sulfur bonds and carbon-sulfur bonds on the surface of the rubber powder molecules are destroyed and broken. After the cross-linked bonds are broken, the three-dimensional cross-linked network structure of the rubber molecules is depolymerized, thereby improving the affinity, adhesion and compatibility between the rubber powder molecules and the matrix interface, and alleviating the phenomenon that the rubber powder vulcanization structure agglomerates and increases the adhesion of the system. However, the destruction of the cross-linked bonds of the rubber powder by simple physical microwave radiation is relatively limited, and it cannot completely depolymerize the rubber powder vulcanization structure. Therefore, this scheme further uses a hydrogen peroxide solution to react with the microwave-treated rubber to perform a carboxylation reaction on the surface of the rubber molecules. Ferrous sulfate can be used as a catalyst to improve the oxidation effect and oxidation performance of hydrogen peroxide. In addition, ferrous sulfate forms sulfate free radicals SO4 in the system. - .; Sulfate radicals can be oxidized and degraded to inhibit the toxic polycyclic substance fluoranthene in asphalt, thereby reducing the smoke release of rubber asphalt. The amphiphilic polymer polyvinyl pyrrolidone is introduced, and its hydrophilic end is compatible with the surface of rubber powder, and its lipophilic end is compatible with asphalt, forming a bridge between rubber powder and asphalt, thereby improving the dispersion and compatibility of rubber powder in asphalt. Finally, microwave activation treatment is used to further enhance the activity of rubber powder; the rubber powder obtained through the above step-by-step reaction is active, has enhanced compatibility with the matrix interface, and reduced adhesion.
[0016] Expanded graphite is a polymer material with strong high temperature resistance. Adding it to rubber asphalt can enhance the thermal stability of the system. When the temperature of the system rises, the porous intercalation structure of the expanded graphite vaporizes due to heat, forming a supporting force for the sheet, causing the expanded graphite sheet to expand, which helps to reduce the viscosity of the asphalt system. The unique porous intercalation structure of expanded graphite can effectively adsorb polycyclic aromatic hydrocarbons such as anthracene and phenanthrene produced in the system, but this adsorption is a physical adsorption process, which only transfers polycyclic aromatic hydrocarbons but does not eliminate them, so the adsorption effect is very limited; titanium dioxide has a photocatalytic oxidation effect, and adding it directly to asphalt will cause agglomeration, resulting in low catalytic efficiency. Therefore, this scheme uses expanded graphite, tetrabutyl titanate, glacial acetic acid, and silicone oil to react to obtain titanium dioxide-modified expanded graphite; when titanium dioxide in titanium dioxide-modified expanded graphite is exposed to light, a photocatalytic oxidation reaction will occur, oxidizing and eliminating organic matter such as polycyclic aromatic hydrocarbons in asphalt; thus greatly reducing the release of polycyclic aromatic hydrocarbons, i.e., smoke, in rubber asphalt. The addition of silicone oil can promote the defoaming of matrix asphalt.
[0017] Styrene-butadiene-styrene block copolymer has excellent thermal stability, and together with activated rubber powder and modified asphalt, it can enhance the thermal stability of rubber asphalt; softening oil as a filler in the system can help reduce the viscosity of rubber asphalt.
[0018] Further, a method for preparing low-viscosity modified rubber asphalt is characterized by comprising the following steps; (1) Take waste tire rubber powder, irradiate with microwave for 60-100 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 2-3 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 75-80°C, react for 15-20 minutes; irradiate with microwave for 25-30 seconds; obtain activated rubber powder; (2) Mix tetrabutyl titanate, anhydrous ethanol and glacial acetic acid, stir, slowly add concentrated sulfuric acid, stir at high speed, the stirring speed is 1000-1500r / min, react for 40-60min; add expanded graphite, heat to 50-55°C, react for 30-40min; heat to 78-82°C, remove anhydrous ethanol, dry, add silicone oil, stir, and obtain a modifier; The base asphalt is heated at a temperature of 185-190°C, stirred, and a modifier is added; high-speed shearing is performed at a shearing speed of 3000-4000 r / min and a shearing time of 40-60 min to obtain a modified asphalt; (3) Mix the modified asphalt and softened oil, stir, and develop for 30 to 40 minutes; add the activated rubber powder and styrene-butadiene-styrene block copolymer obtained in step (1), and stir; heat to 180 to 190°C; shear at a high speed of 3500 to 5000 r / min for 20 to 40 minutes; heat to 205 to 225°C, stir at a high speed for 40 to 50 minutes; maintain constant temperature and develop for 10 to 20 minutes; and obtain low-viscosity modified rubber asphalt.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention uses hydrogen peroxide, ferrous sulfate, polyvinyl pyrrolidone and microwave radiation to activate the rubber powder of waste tires, depolymerize the vulcanized rubber on the surface of the rubber powder, and improve the adhesion and compatibility of the rubber powder with the matrix; it can be evenly dispersed in the molecules, evenly adsorb the light components in the asphalt molecules, and swell to form a bonding structure; and then use expanded graphite, tetrabutyl titanate, glacial acetic acid, and silicone oil to modify the matrix asphalt, improve the thermal stability of the asphalt, and reduce the smoke release in the rubber asphalt. After the above modification reaction, the rubber asphalt finally obtained has low viscosity, good thermal stability, and low odor; it has a wide range of applications. DETAILED DESCRIPTION
[0020] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Example 1 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 78 parts of modified asphalt, 10 parts of activated rubber powder, 12 parts of styrene-butadiene-styrene block copolymer, and 12 parts of softening oil.
[0022] Among them, the mass ratio of base asphalt to modifier is 1:0.008; the particle size of waste tire rubber powder is 40 mesh; and the softening oil is aromatic oil.
[0023] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 60 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 2 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 75°C, react for 15 minutes; irradiate with microwave for 25 seconds; obtain activated rubber powder; (2) Tetrabutyl titanate, anhydrous ethanol and glacial acetic acid are mixed and stirred, concentrated sulfuric acid is slowly added, and the stirring speed is 1000 r / min, and the reaction is carried out for 40 minutes; expanded graphite is added, the temperature is raised to 50°C, and the reaction is carried out for 30 minutes; the temperature is raised to 78-82°C, the anhydrous ethanol is removed, the mixture is dried, silicone oil is added, and the mixture is stirred to obtain a modifier; The base asphalt is heated to 185°C, stirred, and a modifier is added; high-speed shearing is performed at a shearing speed of 3000r / min and a shearing time of 40min to obtain a modified asphalt; (3) Mix the modified asphalt and aromatic oil, stir, and develop for 30 minutes; add the activated rubber powder and styrene-butadiene-styrene block copolymer obtained in step (1), stir; heat to 180°C; shear at a high speed of 3500 r / min for 20 minutes; heat to 205°C, stir at a high speed for 40 minutes; maintain constant temperature and develop for 10 minutes; and obtain low-viscosity modified rubber asphalt.
[0024] Example 2 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 82 parts of modified asphalt, 14 parts of activated rubber powder, 13 parts of styrene-butadiene-styrene block copolymer, and 13 parts of softening oil.
[0025] Among them, the mass ratio of base asphalt to modifier is 1:0.01; the particle size of waste tire rubber powder is 60 mesh; and the softening oil is furfural oil.
[0026] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 60 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 2 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 75°C, react for 15 minutes; irradiate with microwave for 25 seconds; obtain activated rubber powder; (2) Tetrabutyl titanate, anhydrous ethanol and glacial acetic acid were mixed and stirred, and concentrated sulfuric acid was slowly added, stirred at a high speed of 1270 r / min, and reacted for 49 min; expanded graphite was added, the temperature was raised to 52°C, and the reaction was carried out for 35 min; the temperature was raised to 81°C, the anhydrous ethanol was removed, the mixture was dried, silicone oil was added, and the mixture was stirred to obtain a modifier; The base asphalt is heated to 188°C, stirred, and a modifier is added; high-speed shearing is performed at a shearing speed of 3070r / min and a shearing time of 50min to obtain a modified asphalt; (3) Mix the modified asphalt and furfural oil, stir, and develop for 36 minutes; add the activated rubber powder and styrene-butadiene-styrene block copolymer obtained in step (1), stir; heat to 186°C; shear at high speed at a shear rate of 4250 r / min for 27 minutes; heat to 213°C, stir at high speed for 41 minutes; maintain constant temperature and develop for 13 minutes; and obtain low-viscosity modified rubber asphalt.
[0027] Example 3 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 85 parts of modified asphalt, 17 parts of activated rubber powder, 15 parts of styrene-butadiene-styrene block copolymer, and 15 parts of softening oil.
[0028] The mass ratio of base asphalt to modifier is 1:0.03; the particle size of waste tire rubber powder is 80 mesh; and the softening oil is a mixture of cycloparaffin oil and aromatic oil.
[0029] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 100 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 3 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 80°C, react for 20 minutes; irradiate with microwave for 30 seconds; obtain activated rubber powder; (2) Tetrabutyl titanate, anhydrous ethanol and glacial acetic acid were mixed and stirred, concentrated sulfuric acid was slowly added, and the stirring speed was 1500 r / min, and the reaction time was 60 min; expanded graphite was added, the temperature was raised to 55°C, and the reaction time was 40 min; the temperature was raised to 82°C, the anhydrous ethanol was removed, the mixture was dried, silicone oil was added, and the mixture was stirred to obtain a modifier; The base asphalt is heated to 190°C, stirred, and a modifier is added; high-speed shearing is performed at a shearing speed of 4000r / min and a shearing time of 60min to obtain a modified asphalt; (3) Mix the modified asphalt and cyclohexane oil, stir, and develop for 40 minutes; add the activated rubber powder and styrene-butadiene-styrene block copolymer obtained in step (1), stir; heat to 190°C; shear at a high speed of 5000 r / min for 40 minutes; heat to 225°C, stir at a high speed for 50 minutes; maintain constant temperature and develop for 20 minutes; and obtain low-viscosity modified rubber asphalt.
[0030] Comparative Example 1 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 85 parts of modified asphalt, 17 parts of activated rubber powder, 15 parts of styrene-butadiene-styrene block copolymer, and 15 parts of softening oil.
[0031] The mass ratio of base asphalt to modifier is 1: 0.03; the particle size of waste tire rubber powder is 80 mesh; and the softening oil is any one or more of castor oil, aromatic oil, cycloparaffin oil, furfural oil, and rubber filler oil.
[0032] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 100 seconds; add 30% hydrogen peroxide solution, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 3 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 80°C, react for 20 minutes; irradiate with microwave for 30 seconds; obtain activated rubber powder; Steps (2) and (3) are the same as those in Example 3; Comparative Example 2 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 85 parts of modified asphalt, 17 parts of activated rubber powder, 15 parts of styrene-butadiene-styrene block copolymer, and 15 parts of softening oil.
[0033] The mass ratio of base asphalt to modifier is 1: 0.03; the particle size of waste tire rubber powder is 80 mesh; and the softening oil is any one or more of castor oil, aromatic oil, cycloparaffin oil, furfural oil, and rubber filler oil.
[0034] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder and irradiate it with microwave for 100 seconds to obtain activated rubber powder; Steps (2) and (3) are the same as those in Example 3; Comparative Example 3 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 85 parts of modified asphalt, 17 parts of activated rubber powder, 15 parts of styrene-butadiene-styrene block copolymer, and 15 parts of softening oil.
[0035] The mass ratio of base asphalt to modifier is 1: 0.03; the particle size of waste tire rubber powder is 80 mesh; and the softening oil is any one or more of castor oil, aromatic oil, cycloparaffin oil, furfural oil, and rubber filler oil.
[0036] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 100 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 3 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 80°C, and react for 20 minutes; obtain activated rubber powder; Steps (2) and (3) are the same as those in Example 3; Comparative Example 4 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 85 parts of modified asphalt, 17 parts of activated rubber powder, 15 parts of styrene-butadiene-styrene block copolymer, and 15 parts of softening oil.
[0037] The particle size of the waste tire rubber powder is 80 meshes; the softening oil is any one or more of castor oil, aromatic oil, cycloparaffin oil, furfural oil and rubber filler oil.
[0038] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 100 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 3 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 80°C, react for 20 minutes; irradiate with microwave for 30 seconds; obtain activated rubber powder; (2) heating the base asphalt at 190°C, stirring, adding titanium dioxide; high-speed shearing, the shearing speed is 4000r / min, and the shearing time is 60min; and the modified asphalt is obtained; Step (3) is the same as in Example 3.
[0039] Comparative Example 5 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 85 parts of modified asphalt, 17 parts of activated rubber powder, 15 parts of styrene-butadiene-styrene block copolymer, and 15 parts of softening oil.
[0040] The mass ratio of base asphalt to modifier is 1: 0.03; the particle size of waste tire rubber powder is 80 mesh; and the softening oil is any one or more of castor oil, aromatic oil, cycloparaffin oil, furfural oil, and rubber filler oil.
[0041] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 100 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 3 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 80°C, react for 20 minutes; irradiate with microwave for 30 seconds; obtain activated rubber powder; (2) Tetrabutyl titanate, anhydrous ethanol and glacial acetic acid were mixed and stirred, and concentrated sulfuric acid was slowly added. The stirring speed was 1500 r / min and the reaction time was 60 min. Graphene was added and the temperature was raised to 55°C and the reaction time was 40 min. The temperature was raised to 82°C, the anhydrous ethanol was removed, the mixture was dried, silicone oil was added and stirred to obtain a modifier. The base asphalt was heated to 190°C, stirred and the modifier was added. The modified asphalt was obtained by high-speed shearing at a shear speed of 4000 r / min and a shearing time of 60 min. Step (3) is the same as in Example 3.
[0042] Comparative Example 6 The low-viscosity modified rubber asphalt comprises the following raw materials, calculated by weight: 85 parts of modified asphalt, 17 parts of activated rubber powder, 15 parts of styrene-butadiene-styrene block copolymer, and 15 parts of softening oil.
[0043] The mass ratio of base asphalt to modifier is 1: 0.03; the particle size of waste tire rubber powder is 80 mesh; and the softening oil is any one or more of castor oil, aromatic oil, cycloparaffin oil, furfural oil, and rubber filler oil.
[0044] The preparation steps are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 100 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 3 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 80°C, react for 20 minutes; irradiate with microwave for 30 seconds; obtain activated rubber powder; (2) Tetrabutyl titanate, anhydrous ethanol and glacial acetic acid were mixed and stirred, and concentrated sulfuric acid was slowly added. The mixture was stirred at a high speed of 1500 r / min and reacted for 60 min. Carbon nanotubes were added and the mixture was heated to 55°C and reacted for 40 min. The mixture was heated to 82°C, anhydrous ethanol was removed, dried, silicone oil was added and stirred to obtain a modifier. The base asphalt was heated to 190°C, stirred and the modifier was added. The mixture was sheared at a high speed of 4000 r / min and the shearing time was 60 min to obtain a modified asphalt. Step (3) is the same as in Example 3.
[0045] Experimental comparison and analysis In the process of preparing activated rubber in Comparative Example 1, ferrous sulfate was not added to the rubber powder during the activation process, and the asphalt was directly modified; the rest of the contents were the same as those in Example 3; In the process of preparing the activated rubber in Comparative Example 2, the rubber powder was only activated by microwave once; the rest of the contents were the same as those in Example 3; In the process of preparing the activated rubber in Comparative Example 3, the rubber powder was activated by microwave and hydrogen peroxide only once; the rest of the contents were the same as those in Example 3; In the process of preparing modified asphalt in Comparative Example 4, titanium dioxide is directly added instead of this solution, and the rest of the contents are the same as those in Example 3.
[0046] In the process of preparing modified asphalt in Comparative Example 5, graphene is used instead of expanded graphite, and the rest of the contents are the same as those in Example 3.
[0047] In the process of preparing modified asphalt in Comparative Example 6, carbon nanotubes are used instead of expanded graphite, and the rest of the contents are the same as those in Example 3.
[0048] The low viscosity modified rubber asphalt prepared in Examples 1-3 and Comparative Examples 1-6 was tested for performance, and the test data are shown in Table 1 below; 25℃ needle penetration, 0.1 mm Softening point℃ 177℃ viscosity, Pa.s Elastic recovery, % 180℃ bitumen flue gas volatility μg / kg.h Example 1 38 76 1.15 89 1.072 Example 2 38 77 0.96 90 1.021 Example 3 36 79 0.95 90 1.001 Comparative Example 1 45 69 1.98 83 3.805 Comparative Example 2 45 58 4.54 76 3.872 Comparative Example 3 47 68 3.07 71 4.027 Comparative Example 4 46 69 3.57 65 11.745 Comparative Example 5 46 68 3.12 84 5.220 Comparative Example 6 45 68 3.09 86 5.165 Table 1 It can be seen from the data in Table 1 that the viscosity of the modified rubber asphalt prepared in Examples 1-3 at 177°C is about 2.2 Pa.s, and its softening point, elastic recovery and 25°C needle penetration are better than those of the control group, and the asphalt smoke volatilization at 180°C is lower; therefore, it is explained that the rubber asphalt prepared by the technical solution of the present invention has the characteristics of low viscosity, good thermal stability and low smoke release.
[0049] Compared with Example 3, Comparative Example 1 does not add ferrous sulfate, which can catalyze the oxidation of rubber powder by hydrogen peroxide and produce sulfate radicals to eliminate polycyclic hydrocarbons in asphalt. Therefore, the surface activity of the rubber powder in Comparative Example 1 is slightly lower, the adhesion of the rubber powder molecules to the matrix is greater, the viscosity of the prepared rubber asphalt is slightly higher, and the amount of smoke volatilization is increased.
[0050] Compared with Example 3, Comparative Examples 2-3 respectively treat the rubber powder with microwave once, and treat the rubber powder with microwave and hydrogen peroxide synergistically once, while Example 3 treats the rubber powder with microwave once + hydrogen peroxide + microwave twice. It can be seen from the test data that the viscosity of Comparative Examples 2-3 is reduced to varying degrees and the thermal stability is also weakened. Therefore, it is explained that in this scheme, the rubber powder is subjected to microwave once + hydrogen peroxide activation + microwave twice, so that the performance of the rubber powder is optimized, and the prepared rubber asphalt has low viscosity and good stability.
[0051] Compared with Example 3, Comparative Example 4 directly adds titanium dioxide instead of the titanium dioxide-modified expanded graphite in this scheme; the thermal stability of the rubber asphalt prepared thereby is greatly reduced, and the smoke emission is greatly increased; therefore, it also shows that the catalytic oxidation effect of adding titanium dioxide alone is not ideal. In this scheme, the catalytic oxidation effect of titanium dioxide is improved by loading titanium dioxide on expanded graphite. At the same time, expanded graphite is a thermal high-temperature material, which can improve the thermal stability of rubber asphalt.
[0052] Comparative Examples 5-6 are prior art, in which carbon nanotubes or graphene are directly mixed with titanium dioxide to modify asphalt; from the experimental data, it can be seen that these two conventional solutions are weaker than Example 3 in terms of smoke emission and thermal stability.
[0053] In summary, the rubber asphalt prepared by the present invention, that is, the technical solution of the present invention is the best technical solution, and the prepared rubber asphalt has low viscosity, good thermal stability and low odor.
[0054] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A low-viscosity modified rubber asphalt, characterized in that: The invention comprises the following raw materials, by weight: 82 parts of modified asphalt, 14 parts of activated rubber powder, 13 parts of styrene-butadiene-styrene block copolymer, and 13 parts of softening oil; The mass ratio of base asphalt to modifier is 1:0.01; the particle size of waste tire rubber powder is 60 mesh; the softening oil is furfural oil; The preparation steps of the rubber asphalt are as follows: (1) Preparation of activated rubber powder: Take waste tire rubber powder, irradiate with microwave for 60 seconds; add 30% concentration of hydrogen peroxide solution and ferrous sulfate, the mass ratio of hydrogen peroxide solution to waste tire rubber powder is 3:1; react for 2 hours, filter and dry; add polyvinyl pyrrolidone solution, stir, heat to 75°C, react for 15 minutes; irradiate with microwave for 25 seconds; obtain activated rubber powder; (2) Tetrabutyl titanate, anhydrous ethanol and glacial acetic acid were mixed and stirred, and concentrated sulfuric acid was slowly added, stirred at a high speed of 1270 r / min, and reacted for 49 min; expanded graphite was added, the temperature was raised to 52°C, and the reaction was carried out for 35 min; the temperature was raised to 81°C, the anhydrous ethanol was removed, the mixture was dried, silicone oil was added, and the mixture was stirred to obtain a modifier; The base asphalt is heated to 188°C, stirred, and a modifier is added; high-speed shearing is performed at a shearing speed of 3070r / min and a shearing time of 50min to obtain a modified asphalt; (3) Mix the modified asphalt and furfural oil, stir, and develop for 36 minutes; add the activated rubber powder and styrene-butadiene-styrene block copolymer obtained in step (1), stir; heat to 186°C; shear at high speed at a shear rate of 4250 r / min for 27 minutes; heat to 213°C, stir at high speed for 41 minutes; maintain constant temperature and develop for 13 minutes; and obtain low-viscosity modified rubber asphalt.
Citation Information
Cited By
Modified asphalt based on nano material reinforcement and preparation method thereof
CN120059483A